A estratégia do marketing viral no laço social contemporâneo - Maia, Gabriel Monteiro da Fonseca Leal (2014)
The present work had as its main purpose to investigate, under the lacanian psychoanalytic notion of discourse as a form for enjoyment implementation on social bonds, the way in which the modality referred to as "viral marketing" largely employed in the Internet fuses with the technical properties of networked digital media, and its use by the subjects under contemporary capitalist historical context, to yield its diffusing objectives. For such a task, we have first conducted a bibliographical survey, divided into three chapters, and then made an analysis of viral marketing under contemporary social bonds (backed by two cases considered to be successful by professionals in the area). Regarding the researched bibliography, we first establish the relations between capitalism and discourses, sustained by views drawn from Jacques Lacan and other authors in Psychoanalysis. We then focus on the historic developments of strategies for stimulating consumption, especially held by advertising and marketing companies, and their merging with the technical developments of 20th century media and the advent of viral marketing. Later, we investigate the transformations held inside the capitalist mode of production and the abstraction of commodities in brands, examining how these transformations relate to contemporary media system and its use by the subjects. Finally, we place viral marketing under the social bond of the Discourse of the Master, where the market induces the know-how of social network users to spread media content amongst its social circles, propagating both image and brand s name (the virus)